Job Satisfaction of Teachers in Regular Basic Education Institutions: A Bibliometric Approach - Espejo-Chacon, Luis Fernando; Miranda, Cecilia Celeste Mendoza Aguilar de; Pacheco-Torres, Julio Enrique; Gonzales-Rentería , Yuri Gagarín (Journal of Ecohumanism, 2025)
This study analyzed the literature on job satisfaction among elementary school teachers, published in Scopus between 2018 and 2023, using bibliometric indices. A search was conducted using the keywords "job satisfaction," "teachers," and "elementary school," applying open access filters and limiting the period to 2019-2023, without geographical restrictions. A total of 35 studies were selected for analysis, exported in Bibtex format, and processed with Cran-R. The results showed that 2021 and 2019 were the years with the highest scientific production, with 9 and 8 studies, respectively. Four authors stood out for their continued research on the subject. Indonesia had the highest number of publications, followed by the United States. Additionally, the "International Journal of Instruction" was the most frequently published journal, with 3 articles. The study explored the relationship between keywords, authors, publication sources, and other bibliometric indicators, such as documents published with DOI and their citations per year. The study concluded that the topic of job satisfaction among teachers requires greater academic attention, as it is crucial for improving and innovating continuous education worldwide.